1992
DOI: 10.2307/1369209
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Avian Life Histories: Effects of Experimentally Elevated Testosterone on Prebasic Molt and Survival in Male Dark-Eyed Juncos

Abstract: Male Dark-eyed Juncos (Junco hyemalis) that breed in Virginia begin their prebasic molt after breeding has ended, usually in August. Almost all males caught in late October have completed the molt. In 1989, we obtained anecdotal evidence that males whose testosterone (T) we maintained at artificially elevated levels beyond the end of the breeding season postponed or suppressed prebasic molt. To test the effect of T experimentally, in spring 1990 we implanted some males (T-males) with testosterone and others (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 21 publications
2
62
2
Order By: Relevance
“…Removal as late as October also did not influence survival (50% T vs. 50% C; Nolan et al 1992). However, when implants were not removed, T-males were significantly less likely than C-males to return (20% T vs. 43% C; Nolan et al 1992). We conclude that suppression of molt or some other consequence of elevated T in autumn resulted in higher mortality of T-males.…”
Section: Fitness Consequences Of Treatment With Testosteronementioning
confidence: 68%
See 3 more Smart Citations
“…Removal as late as October also did not influence survival (50% T vs. 50% C; Nolan et al 1992). However, when implants were not removed, T-males were significantly less likely than C-males to return (20% T vs. 43% C; Nolan et al 1992). We conclude that suppression of molt or some other consequence of elevated T in autumn resulted in higher mortality of T-males.…”
Section: Fitness Consequences Of Treatment With Testosteronementioning
confidence: 68%
“…Thus, the consequence of experimentally elevating testosterone has been to shift male reproductive effort away from care of offspring toward other forms of reproductive effort, such as singing and sexual and aggressive behavior (e.g., Beletsky et al 1995; see citations in table 1). In some cases, elevation of testosterone has also compromised male sur- Nolan et al 1992 vival or produced phenotypic changes that would seem likely to have that effect (e.g., ; see citations in table 1).…”
Section: Testosterone Mating Effort and Parental Effort In Birdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nilsson & Svensson (1996) suggested that the reduction in over-winter survival and subsequent breeding success of late-moulting blue tits were caused by increased thermoregulatory costs due to poorer feather quality. However, Nolan et al (1992) found no di¡erence in over-winter survival of dark-eyed juncos, Junco hyemalis, in which moult was delayed by testosterone implants, although, not surprisingly, survival was markedly reduced in birds that were prevented from moulting. The subsequent breeding performance of the late-moulting juncos was not reported.…”
Section: Discussionmentioning
confidence: 78%